The impact of the awareness of being hiv seropositive on partürients - Sampaio Neto, Luiz F.; Silva, Sérgio C.; Condi, Gustavo G.; Pinto, Pérsio C.C.; Novo, Neil F. (Brazilian Journal of Sexually Transmitted Diseases, 2002)
The objective of the present study was to determine whether being previously aware of their HI V+ status modifies the obstetrical course of the parturients and the involvement of the conceptus. We analyzed all the Hl V+ parturients attended at the Maternity of the Sorocaba Faculty of Medicine, from January1997 to December 2000. Many of them were already aware of being HIV+ and those who did not know their serologic status were submitted to the rapid test at the time of admission for delivery, they were retrospectively classified into two groups: women who already knew their HIV+ statuts and women who learned about their HIV+ status! upon admission for delivery. Data were analyzed statistically by the Mann-Whitney test (age), by the Pearson chi- square test (epidemiological variables, and obstetrical/neonatal aspects), by the partition chi-square test (use of vitamin supplements, use of AZT and untoward events affecting the conceptus), and by the exact Fisher test (alcoholism). A total of 131 parturients were found to be 111V+ during the study period, with 95 of them (72,5%) being aware of their Hl V+ status before admission to the maternity (group I) and 36 (27.5%) ignoring their serological situation (group 2). The groups were similar in terms of the epidemiological variables studied, and were similar in terms of obstetrical data. Group 2 parturients had a larger number of untoward events during pregnancy (more urinary infections, anemia, arterial hypertension, premature rupture of the fetal membranes, and STD). Group 1 parturients used prenatal vitamin supplementation in a more adequate manner, received AZT more frequently at the time of delivery, and were submitted more frequently to tube ligation at the time of delivery.